Damong ligaw - Avellana, Jose Mari; Sarmenta, Romnick; Tamayo, Beth; Lazaro, Ronnie; Premiere Productions (Firm). ([Place of production not identified] Premiere Productions, 1997)
"A confused and angry farm boy brought up under the strict and seemingly unforgiving guidance of an exacting and domineering father gains initiation to both romance and heroism during the Philippine Revolution of 1896."
Summary taken from: https://www.imdb.com/title/tt0436207
Produced by Boots Anson-Roa; music by Irwin Cafugauan; cinematography by Ricardo Remias.
Romnick Sarmenta, Beth Tamayo, Ronnie Lazaro.
DVD
In Tagalog
Keywords: Action; Drama